小児核医学検査における99mTc-DMSA シンチグラフィの適正投与量の検証を目的とした画質評価ファントムの開発 - 杉本, 勝也; 村川, 圭三; 市川, 肇; 小野口, 昌久; 長木, 昭男; 安藤, 猛晴; 河村, 誠治; 菊池, 敬; 西村, 圭弘 (Nippon Hōshasen Gijutsu Gakkai zasshi, 2017)
Purpose: We conducted a field survey about pediatric nuclear medicine. As a result, it was suggested that 99mTc-DMSA scintigraphy was performed at many institutions, whereas various examinations such as image acquisition and processing are not carried out using the renal phantom. Therefore, we developed the body phantom for the evaluation of appropriate administered radioactivities and image quality with renal scintigraphy in pediatric nuclear medicine. Methods: We created three differently sized body phantoms (1-, 5-, and 20-year-old models). These pediatric body phantoms were filled with a 99mTc solution based on the consensus guideline of pediatric radiopharmaceutical administered radioactivity in Japan. The planar image was evaluated using acquisition count, uniformity and defect contrast. SPECT images were evaluated with a recovery coefficient (RC). Results: The acquisition counts for pediatric body phantoms were relatively corresponded to the clinical study. The appropriate acquisition counts and the pixel size for the planar image were approximately 140 counts per pixel and 1.23–1.35 mm at 5 min acquisition times in 1- and 5-year-old pediatric body phantom studies, respectively. Although the uniformity and the cold contrast did not depend on pixel size and body size, the cold contrast was affected by body size. The RC for SPECT images depended on the performance of SPECT systems, the resolution recovery algorithm and body phantom size. Conclusion: The developed pediatric body phantom could allow us to establish optimal image acquisition and more evidence on renal scintigraphy in pediatric nuclear medicine.